Revealing the invisible dead: integrated bio-geoarchaeological profiling exposes human and animal remains in a seemingly 'empty' Viking-Age burial. (May 2022) - Sulas, Federica; Bagge, Merethe Schifter; Enevold, Renée; Harrault, Loïc; Kristiansen, Søren Munch; Ljungberg, Thomas; Milek, Karen B.; Mikkelsen, Peter Hambro; Jensen, Peter Mose; Orfanou, Vana; Out, Welmoed A.; Portillo, Marta; et al.
Abstract: Recent investigations of an apparently 'empty, ' partly disturbed Viking chamber grave in Denmark (Fregerslev II, dated around the mid-10th century CE) provided an opportunity to develop a novel multi-scale and multi-method analysis of burial and post-burial processes. To overcome the limitations of poor preservation of artefacts and bones, and the lack of a clear macrostratigraphic sequence, we integrated multi-proxy analyses of organic and inorganic materials to study the spatial architecture, burial, and post-depositional processes, including soil chemistry (inductively coupled plasma mass spectrometry - ICPMS, portable X-ray fluorescence spectrometer - pXRF), soil micromorphology, archaeobotany (wood, seeds, fruits, phytoliths), palynology (pollen, non-pollen palynomorphs), and faecal lipid biomarkers. The results enabled the detailed characterisation, spatial analysis, and sequencing of burial deposits, and the identification of post-depositional factors responsible for the poor preservation of the burial. Soil, phytolith and pollen data indicated that the base of the grave was covered with a matting of plant material, and there was no wooden floor. Faecal biomarkers detected substantial amounts of faecal matter, most probably originating from horse faeces, suggesting that a horse died in situ, and trace amounts of pig faeces, which are more likely to have been trampled into the grave. Enriched phosphorus concentrations could be linked to the bodies in the northern and southern sector of the grave. Furthermore, enrichment in lead was found where metal objects were recovered. The findings from Fregerslev II show that integrating high-resolution approaches to the analysis of poorly preserved burial contexts can fundamentally transform archaeological interpretations. Highlights: Multi-proxy analyses reveal burial practices at a Viking grave with no bone preserved. Geochemistry, micromorphology, archaeobotany and palynology define spatiotemporal burial processes. Faecal biomarkers and elemental mapping detect traces of human and horse inhumations. Soil, archaeobotanical and palynological data show a bedding of grass and herbs on the grave base.